2013
DOI: 10.1016/j.mehy.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment of epilepsy with ketogenic diet and concurrent pharmacological inhibition of cytochrome P450 2E1

Abstract: While most epileptic patients respond to treatment with existing antiepileptic drugs, there remains a considerable number of patients in whom these drugs do not suffice. Such patients, particularly children, are often treated using the ketogenic diet. This diet imposes a strict limit on carbohydrates; while providing for adequate protein, most of the calories are supplied as triacylglycerol, much of which is metabolized to ketone bodies.Animal experiments have provided evidence that the anticonvulsant effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…It has been shown that 60 day old GK rats developed increased ketone body production [ 47 ], however, there is no literature data available about ketone body metabolism in the heart of GK rats. The ketone body acetone can be converted in vivo to glucose via acetol and pyruvate, and the initial conversion to acetol is catalyzed by Cyp2e1 [ 48 ]. It has been shown that Cyp2e1 knockout mice subjected to starvation to induce ketogenesis develop blood acetone levels much higher than those observed in wild-type mice [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that 60 day old GK rats developed increased ketone body production [ 47 ], however, there is no literature data available about ketone body metabolism in the heart of GK rats. The ketone body acetone can be converted in vivo to glucose via acetol and pyruvate, and the initial conversion to acetol is catalyzed by Cyp2e1 [ 48 ]. It has been shown that Cyp2e1 knockout mice subjected to starvation to induce ketogenesis develop blood acetone levels much higher than those observed in wild-type mice [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ketone body acetone can be converted in vivo to glucose via acetol and pyruvate, and the initial conversion to acetol is catalyzed by Cyp2e1 [ 48 ]. It has been shown that Cyp2e1 knockout mice subjected to starvation to induce ketogenesis develop blood acetone levels much higher than those observed in wild-type mice [ 48 ]. In our present study, the down-regulation of Cyp2e1 might be a possible cause of increased ketone body level in the myocardium, however, up-regulation of other genes involved in ketone metabolic process including Aldh1a1 ; Adh1c ; Akr1b10 ; and Akr1c12 may be an adaptive response in the myocardium to antagonize elevated ketone body levels.…”
Section: Discussionmentioning
confidence: 99%
“…Pioglitazone is metabolized by CYP2C8 and CYP3A4, 26 but currently there is no evidence that the KD regulates these enzymes. Conversely, one of the metabolic pathways of the putative biochemical effectors of the KD, acetone and polyunsaturated fatty acids, involves CYP1 and CYP2 enzymes, which are inhibited by pioglitazone [27][28][29] ; thus, KD constituents could increase with adjuvant treatment with pioglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has employed a combined treatment approach to epilepsy using both the ketogenic diet and pharmacological inhibition of CYP2E1, which causes an increase of blood acetone levels (a ketone that is also increased by the ketogenic diet). This increase in acetone levels may significantly increase antiepileptic effects of the ketogenic diet (Palmer, 2013). A similar approach could be taken with the 3.2:1 ketogenic diet and its ability to alleviate behavioral symptoms of ASD.…”
Section: Magnitude Of Blood Chemistry Changesmentioning
confidence: 99%